1993
DOI: 10.1007/bf01526797
|View full text |Cite
|
Sign up to set email alerts
|

Local antitumour treatment in carcinoma patients with bispecific-monoclonal-antibody-redirected T cells

Abstract: In a pilot clinical study carcinoma patients with malignant ascites or pleural exudates have been treated locally with autologous lymphocytes activated ex vivo and redirected towards tumour cells with bispecific monoclonal antibodies. BIS-1, the bispecific monoclonal antibody used in this study, combines specificity against a tumour-associated antigen, AMOC-31, present on carcinomas, with a specificity against the CD3 complex on T lymphocytes. Patients selected for treatment had malignant pleural or peritoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…28 Two studies have already reported encouraging results with bispecific antibodies in combination with pre-activated PBL in patients with ovarian cancer. 29,30 These approaches induced local inflammatory reactions and even tumor regression, but were lim- ited by the need for in vitro stimulation of effector cells. A study was published recently demonstrating that effector lymphocytes within malignant ascites, without prior stimulation, can be used together with i.p.…”
Section: Discussionmentioning
confidence: 99%
“…28 Two studies have already reported encouraging results with bispecific antibodies in combination with pre-activated PBL in patients with ovarian cancer. 29,30 These approaches induced local inflammatory reactions and even tumor regression, but were lim- ited by the need for in vitro stimulation of effector cells. A study was published recently demonstrating that effector lymphocytes within malignant ascites, without prior stimulation, can be used together with i.p.…”
Section: Discussionmentioning
confidence: 99%
“…BIS is an EpCAM-directed CD3-agonistic bsAb. 38 This modification allows for redirecting the Jurkat.PD1-NFAT-luc T cells towards EpCAM + A431 carcinoma cells. In short, Jurkat.PD1-NFAT-luc T cells were mixed BIS-1-pretreated A431 cells at a cell ratio of 5 to 1 and then cultured for 18 h in the presence of PD-L1xEGFR or appropriate control antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…EGP2 (also known as hEGP314, GA733-2 antigen, KSA, EGP40) is a 38-kDa transmembrane glycoprotein expressed on the surface of most simple epithelial cells and the majority of carcinomas such as colorectal, lung and breast carcinomas . MAbs directed against EGP-2, such as C017-lA, KS1/4 and MOC3 1, have been studied extensively in diagnostic and therapeutic approaches in cancer (Lobuglio et al, 1986;Elias et al, 1990; Kroesen et al, 1993;Herlyn et al, 1994;Kosterink et al, 1995). The human EGP2 cDNA was independently cloned by different research groups (Bumol et al, 1988;Strnad et al, 1989;Szala et al, 1990) and, more recently, its gene structure on chromosome 4q has been partly determined.…”
mentioning
confidence: 99%